Critical top management supports that influencing the project success in construction industry - Danial, Muhammad Hafizi (2020)
The misalignment between the organization and its operational objectives and strategies are resulted from several shortcomings such as unclear roles and responsibilities, limited autonomy and accountability, lack of a commercial and customer orientation, and weak of professional capacity, which put project success at stake. Top management who holds the ultimate source of authority in an organization have to be responsible for the overall business direction and success. This study was conducted as an attempt to provide solutions to overcome these challenges in project implementation. The objectives of this study are to identify the importance factors of top management support to influence on project success, to investigate the relationship between top management support and project success, and to determine the critical top management support that influencing the project success. The scope of this study was focused within Construction Industry located in Johor Bahru area. The samples of this study are constituted of people who serve in project based organization or project oriented organization, and they hold various position from top management to executive level. The research methodology of this study was designed by employing quantitative research approach, with relevant data gained from the responses of online survey form established in ?Google Form? system. The data were analysed using three different methods which are descriptive mean analysis, correlation analysis and regression analysis for each research‘s objective. The findings of this study show that top management should prioritize their strategies on three main areas namely financial system, stakeholder management and macro-economic factor. This study also discovers that top management should adopt all quality of top management supportive behaviours proportionally to ensure the effect of their actions are impactful to influence on project success. This is very true as demonstrated by the correlation results which indicate very significant positive relationships between combination of all top management support behaviours and three different areas of project success namely future preparation, project efficiency, and business adaptability and success. On the other hand, the regression analysis gives another indicator to suggest the critical top management strategies to be adopted in attempt to highly influence on project success. Top management should give more priority on development of effective communication system to improve the information transfer and message interpretation between project team and top management level. Even though a focus on single strategy may work for project efficiency‘s success, but communication system alone may not be feasible to attain the project success in business adaptability and success. Top management should blend the communication management strategy with organizational structural arrangement strategy to ensure their organization and its project strategy are adaptable with the current economic situation. Another critical area of project success of future preparation seek for a wider spectrum of top management support strategies which to employ organizational structural arrangement strategy, resources management strategy, top management power strategy and communication management strategy. The last part of project success spectrum which is customer satisfaction demonstrated different outcome relative to the other project success spectrum. The results show that top management support may not provide impactful results in pursuing customer satisfaction.